2012
DOI: 10.1183/09031936.00062512
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser endomicroscopy for diagnosing lung cancerin vivo

Abstract: Confocal laser endomicroscopy is a novel endoscopic technique that may allow imaging of living cells in lung tissue in vivo. We assessed the potential of this technique for the detection of histology during screening bronchoscopy for lung cancer.32 patients with suspected malignancies underwent bronchoscopy with endomicroscopy using acriflavine hydrochloride. Standardised areas and localised lesions were analysed by in vivo confocal imaging during bronchoscopy and biopsies were taken. Confocal images were grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 27 publications
3
85
0
3
Order By: Relevance
“…The accurate analysis of confocal microstructure of intrapulmonary tissues can help to precisely localize a biopsy site, significantly improving the diagnostic yield of bronchoscope biopsy. The exploration of CLE for neoplastic changes could be predicted with a sensitivity of 96.0%, specificity 87.1% and accuracy 91.0% (2). In these two cases, the radial probe endobronchial ultrasound was used to perform exploration and confirm the lesion located outside the lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate analysis of confocal microstructure of intrapulmonary tissues can help to precisely localize a biopsy site, significantly improving the diagnostic yield of bronchoscope biopsy. The exploration of CLE for neoplastic changes could be predicted with a sensitivity of 96.0%, specificity 87.1% and accuracy 91.0% (2). In these two cases, the radial probe endobronchial ultrasound was used to perform exploration and confirm the lesion located outside the lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (1,2) reported that CLE is promising for lung cancer exploration and improving diagnostic yield. Compared to the conventional probe-based confocal laser endomicroscopy (pCLE), the novel needle-based confocal laser endomicroscopy (nCLE) is characterized by a smaller miniprobe (AQ-Flex 19, Mauna Kea Technologies, Paris, France) with an external diameter of 0.9 mm, a resolution of 3.5 µm and a penetration depth of 40 to 50 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors tried to use contrast agents such as fluorescein and acriflavine hydrochloride to improve the detection of epithelial bronchial cells during bronchoscopy in patients with suspected lung cancer (47,48). In particular Fuchs et al demonstrated that the diagnostic value of acriflavine-aided CLE was comparable to the histology of lung biopsies, predicting the presence of neoplastic changes with a sensitivity of 96%, a specificity of 87.1% and an accuracy of 91% (48).…”
Section: Clementioning
confidence: 99%
“…In pulmonology, CLE has been used for early detection of neoplastic changes in the bronchial tree with a high accuracy (91.0%) [24]. In urology, marked differences in microanatomical structures have been reported for normal urothelium and high-grade tumours [35], and diagnostic criteria to facilitate interpretation of CLE images have been defined [36].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…They are easily applied and do not regularly carry the risk of systemic side effects, yet no agent is officially licensed for in-vivo use in humans and they typically do not penetrate deeply into the mucosa [3]. The most commonly used agent is acriflavine [22][23][24], which stains the nuclei and is typically applied as acriflavine hydrochloride 0.05%. By combining fluorescein and topical acriflavine, it is possible to calculate nuclear cytoplasmatic ratios, which is a useful indicator for cellular differentiation.…”
Section: Fluorescent Contrast Agents For Confocal Laser Endomicroscopymentioning
confidence: 99%